Howl's moving castle [videorecording (DVD)] - Kimura, Takuya, 1972-; Baishō, Chieko; Gashūin, Tatsuya, 1950-; Jones, Diana Wynne (Shout Factory, 2017)
Sophie, a quiet girl working in a hat shop, finds her life thrown into turmoil when she is literally swept off her feet by a handsome but mysterious wizard named Howl. The vengeful Witch of the Waste, jealous of their friendship, puts a spell on Sophie. In a life changing adventure, Sophie climbs aboard Howl's magnificent moving castle and enters a magical world on a quest to break the spell.